2006
DOI: 10.1007/s10641-006-9135-z
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of steelhead (Oncorhynchus mykiss) in the Klamath River

Abstract: An analysis of population structure and genetic diversity was conducted on samples of Oncorhynchus mykiss (steelhead/rainbow trout) from 33 sites in the Klamath-Trinity River basin. Genotype data from 16 microsatellite loci in almost 1,700 fish revealed genetic differentiation between most sampled locations. Two pairs of samples from the same sites in different years were not significantly different, indicating stability of population structure, at least on a short time scale. Most sampling sites were genetica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 16 publications
(14 reference statements)
13
18
0
Order By: Relevance
“…This pattern is consistent with previous studies of coastal steelhead, which found similar signals of IBD Garza et al 2014). A similar pattern of structuring by geography and not phenotype has also been observed in other anadromous and resident O.mykiss populations (Docker et al 2003;Olsen et al 2006;Pearse et al 2007;Clemento et al 2009). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This pattern is consistent with previous studies of coastal steelhead, which found similar signals of IBD Garza et al 2014). A similar pattern of structuring by geography and not phenotype has also been observed in other anadromous and resident O.mykiss populations (Docker et al 2003;Olsen et al 2006;Pearse et al 2007;Clemento et al 2009). …”
Section: Discussionsupporting
confidence: 91%
“…Microsatellite markers are highly polymorphic and informative, have a long history of use in population genetics (Sunnucks 2000), and have been used extensively to study O. mykiss populations (e.g Heath et al 2002;Hauser et al 2006;Pearse et al 2007Pearse et al , 2009Clemento et al 2009;Martínez et al 2011;Garza et al 2014). However, because of the ease of genotyping and portability of the resulting data, single nucleotide polymorphism (SNP) markers are increasingly used in population genetic investigations (Morin et al 2004), including to assess population demography, estimate phylogenetic relationships and for parentage analysis (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Patterns of genetic divergence based on the 32 non-Omy5 loci, as measured by F ST and phylogenetic network analysis (electronic supplementary material, figure S1), were consistent with previous studies showing close relationships between populations above and below barriers within a watershed and increasing divergence with distance along the California coast [39,40,[57][58][59][60]. By contrast, analysis of loci located on Omy5 showed high divergence between above-and belowbarrier populations within the same basin, and nearly complete reciprocal monophyly between above-and below-barrier populations (electronic supplementary material, figure S1).…”
Section: (B) Population Structuresupporting
confidence: 88%
“…salmonids (Palstra et al 2007), including California steelhead (Garza et al 2004;Pearse et al 2007), cod (Pogson et al 2001), oysters (Peterson and Denno 1998), insects (Rose et al 2006), and plants (CruseSanders and Hamrick 2004), but see Pearse et al (2006) for an exception in turtles). However, without a historical reference point, there is no way to know if the populations are in migration-drift equilibrium or representative of their natural state.…”
Section: Discussionmentioning
confidence: 99%